Second-best justice : the virtues of Japanese private law - Ramseyer, J. Mark, 1954- (University of Chicago Press, 2015)
It's long been known that Japanese file fewer lawsuits per capita than Americans do. Yet explanations for the difference have tended to be partial and unconvincing, ranging from circular arguments about Japanese culture to suggestions that the slow-moving Japanese court system acts as a deterrent. With Second-Best Justice, J. Mark Ramseyer offers a more compelling, better-grounded explanation: the low rate of lawsuits in Japan results not from distrust of a dysfunctional system but from trust in a system that works--that sorts and resolves disputes in such an overwhelmingly predictable pattern that opposing parties rarely find it worthwhile to push their dispute to trial. Using evidence from tort claims across many domains, Ramseyer reveals a court system designed not to find perfect justice, but to "make do"--To adopt strategies that are mostly right and that thereby resolve disputes quickly and economically. An eye-opening study of comparative law, Second-Best Justice will force a wholesale rethinking of the differences among alternative legal systems and their broader consequences for social welfare